2011
DOI: 10.1371/journal.pone.0021078
|View full text |Cite
|
Sign up to set email alerts
|

OSBP-Related Protein 8 (ORP8) Regulates Plasma and Liver Tissue Lipid Levels and Interacts with the Nucleoporin Nup62

Abstract: We earlier identified OSBP-related protein 8 (ORP8) as an endoplasmic reticulum oxysterol-binding protein implicated in cellular lipid homeostasis. We now investigated its action in hepatic cells in vivo and in vitro. Adenoviral overexpression of ORP8 in mouse liver induced a decrease of cholesterol, phospholipids, and triglycerides in serum (−34%, −26%, −37%, respectively) and liver tissue (−40%, −12%, −24%), coinciding with reduction of nuclear (n)SREBP-1 and -2 and mRNA levels of their target genes. Consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 52 publications
4
50
1
1
Order By: Relevance
“…ORP8 was previously shown to localize to the ER and nuclear envelope (11,12). We found that ORP8 was also distributed to the hepatocyte plasma membrane.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…ORP8 was previously shown to localize to the ER and nuclear envelope (11,12). We found that ORP8 was also distributed to the hepatocyte plasma membrane.…”
Section: Discussionmentioning
confidence: 50%
“…Cell Lines-Our previous study demonstrated that ORP8 overexpression in mouse liver significantly reduces the plasma total cholesterol level in vivo (12). Because aberrant elevation of the cholesterol level is associated with various types of cancers (16), a total of 67 clinical HCC samples were analyzed for ORP8 expression for both mRNA and protein expression by qRT-PCR and Western blot.…”
Section: Orp8 Protein Is Down-regulated In Human Hcc Tissues Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic StAR expression was increased 7-and 15-fold in steatosis and NASH patients, respectively 11 , thereby enhancing mitochondrial free cholesterol accumulation and toxicity Heterozygous NPC1/2 deficiency leads to fatty liver, obesity and metabolic syndrome 82 NPC1 gene is linked to to early-onset and morbid adult obesity in Europeans 83 ORP8 ↓ hepatic cholesterol and triglyceride accumulation by inhibiting activation of SREBP-2 and SREBP-1c ORP8 ↑ hepatic insulin sensitivity through an AKTmediated mechanism 86,87 Cholesterol absorption and secretion [39][40][41] 25OHC3S had opposite effects than 25OHC on lipid metabolism and inflammation and improved NAFLD in cellular and mouse models( [39][40][41] Enhancement of on of SULT2B1b activity may counteract effects of toxic oxysterols …”
Section: Biological Effectmentioning
confidence: 99%
“…ORP8 negatively regulates ABCA1 expression and macrophage cholesterol efflux (Yan, Mayranpaa et al 2008). ORP8 has the capacity to modulate lipid homeostasis and SREBP activity, probably through an indirect mechanism required Nup62 (Zhou, Li et al 2011). The OSBPL8-ZDHHC17 region (chr12) is detected for HDL cholesterol identified by one new SNP with genome-wide significance (Ma, Yang et al 2010).…”
Section: Overview Of Functions Of Osbp/orp Family Proteins and Their mentioning
confidence: 99%